What is New on Curriculum Policy and How it Affects Curriculum Studies? - Subkhan, Edi (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
In many countries the development of curriculum always in relation to the politic and the intervention of the government. Furthermore, it brings complexities in practices when the teachers try to implement the national-official curriculum in schools’ context, because there are many tensions among the interest of the government, the teachers’ ability to perceive and develop the curriculum on a contextual way, the slow and conservative bureaucracy in the district level, and the empirical social phenomenon and changes in the field. For instance in Indonesia, the rise of the national curriculum of 2013 is not academic in nature, but more political and we could see how the government takes many issues from the international trend to enrich the content of the curriculum and it implementation (see i.e. Alhamuddin, 2019; Mitra & Purnawarman, 2019; Perdana, 2013). The government role on developing the national curriculum is interesting, especially because it has a power and system to force the schooling system to accept and implement the official curriculum by enacting several policies. For me it is also interesting to questioning whether the government perceived the curriculum as a field of studies or only as a public policy? In Indonesian context this understanding is important, because could be the important cause of the stagnation of the development of Curriculum Studies in general (Subkhan, 2019). According to the this issue, the edited book by Priestly and Biesta (2013) is important, because it elucidates the recent development of curriculum policy and how it has been practiced and developed in many ways in many countries throughout the world. It is relevant to know the position and role of curriculum policy in the development of curriculum at national level and its affects to Curriculum Studies as well.